Accessibility Fund as a part of a system to ensure accessibility for people with special needs - Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu, 2021)
The article deals with the Accessibility Fund which is a part of a system of ensuring accessibility for people with special needs. One of the basic tasks of the state is to remove barriers and ensure accessibility for all citizens, including people with mobility or perception difficulties. The Accessibility Fund is a state purpose fund. This fund has statutorily defined revenues and expenditures. It is a fund of relatively low financial significance. The study argues that the state’s tasks in the area of an accessibility could be effectively fulfilled without the establishment of this fund, and its role could be taken over by one of the existing special purpose funds.